Evaluation on material structural scarcity resource towards sustainable supply chain performance - Kamarudin, Nurhayati; Nizam, Nurul Zarirah; Mohd Sam, Mohd Fazli (Qazvin Islamic Azad University, 2022)
Supply Chain Performance refers to the extended supply chain's activities in meeting end-customer requirements, including product availability, on-time delivery, and all the necessary inventory and capacity in the supply chain to deliver performance responsively. The issue of inequality and extended consumption in supply and demand become crucial since the pandemic COVID-19. Plus, the increase of population enforces manufacturing to examine the sustainable effect to overcome the business impact. Therefore, anticipated with Sustainable Supply Chain Performance (SSCP) to plan an initiative of material scarcity to have a better performance in the supply chain to contribute to economic and social advantage. The objectives of this study; to investigate the level of SSCP in Material Scarcity Resources, to explore the implications of material scarcity resources for companies in structural scarcity towards sustainable supply chain performance and finally to investigate the impact of material scarcity resources in SSCP in environmental, economic and social in Malaysia. A total of 101 respondents among manager level from the southern region of Malaysia’s manufacturing industry was collected. The result showed that Material Structural Scarcity Resource has a positive effect on environmental, economic, and social performance in a sustainable supply chain. Thus, sustainable supply chain performance showed consistency in the performance into the material scarcity overcomes, reducing inventory which enhances the productivity, environmental initiatives advance into product innovation and cut costs reductions. As a result of the factor analysis in the components environmental legislation demand with 89.7% showed that the sustainable supply chain performance significantly improved on the stages of manufacturing, increase diversity of products, lowering manufacturing price, increasing market share, introducing new products rapidly and be the forefront of the future legislation demands. So, it is beneficial to the manufacturing industry companies in improving their performance and stabilizing the economic condition indirectly.